Slaughterhouse wastewater treatment: a case study in Mexico - NA, NA (2026)
[Introduction]: Slaughterhouses are facilities where animals are slaughtered for meat and other products. The wastewater generated in these establishments impacts on the environment and public health due to its high organic matter content, nutrients (nitrogen and phosphorus), and pathogens when discharged untreated. Therefore, the proper management of these wastewaters is crucial to ensure the protection of human health. [Objective]: To propose a treatment system for wastewater from a municipal slaughterhouse, taking Zacualpan de Amilpas in the state of Morelos, Mexico, as a case study. [Methodology]: A representative sample of the slaughterhouse wastewater was characterized physicochemically and biologically. Based on the results, a treatment system was designed, a prototype was built to treat the effluent, and the treated water was characterized, comparing the results with the quality limits established in official Mexican standards. [Results]: Total suspended solids, settleable solids, chemical oxygen demand, total nitrogen, and fecal coliforms exceeded quality limits by 536 %, 1 250 %, 566 %, 2 846 %, and 480 %, respectively. Escherichia coli was also present. A prototype treatment system based on sedimentation, coagulation-flocculation, activated sludge, and disinfection was proposed and built. High removal efficiencies (89.9 % – 99.9 %) were achieved for most parameters outside the standard. Only total nitrogen showed an efficiency of 67.5 %, remaining outside the quality limits. [Conclusions]: The proposed treatment system was favorable, achieving efficient removal percentages. However, an anoxic reactor could be included in the system to reduce nitrogen below quality limits.